Feddersen and Pesendorfer meet Ellsberg - Matthew Ryan (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2019)
The Condorcet Jury Theorem formalises the "wisdom of crowds": binary decisions made by majority vote are asymptotically correct as the number of voters tends to infinity. This classical result assumes like-minded, expected utility maximising voters who all share a common prior belief about the right decision. Ellis (2016) shows that when voters have ambiguous prior beliefs – a (closed, convex) set of priors – and follow maxmin expected utility (MEU), such wisdom requires that voters' beliefs satisfy a "disjoin posteriors" condition: difference private signals lead to posterior sets with disjoint interiors. Both the original theorem and Ellis's generalisation assume symmetric penalties for wrong decisions. If, as in the jury context, errors attract asymmetric penalties, then it is natural to consider voting rules that raise the hurdle for the decision carrying the heavier penalty for error (such as conviction in jury trials). In a classical model, Feddersen and Pesendorfer (1998) have shown that, paradoxically, raising this hurdle may actually increase the likelihood of the more serious error. In particular, crowds are not wise under the unanimity rule: the probability of the more serious error does not vanish as the crowd size tends to infinity. We show that this "Jury Paradox" persists in the presence of ambiguity, whether or not juror beliefs satisfy Ellis's "disjoint posteriors" condition. We also characterise the strictly mixed equilibria of this model and study their properties. Such equilibria cannot exist in the absence of ambiguity but may exist for arbitrarily large jury size when ambiguity is present. In addition to "uninformative" strictly mixed equilibria, analogous to those exhibited by Ellis (2016), there may also exist strictly mixed equilibria which are "informative" about voter signals.
Keywords: 330